Infectious and parasitic diseases of poultry in Ethiopia: A systematic review and meta-analysis - Asfaw, Y.; Ameni, G.; Medhin, G.; Alemayehu, Gezahegn; Wieland, Barbara (Elsevier, 2019)
In Ethiopia, poultry production is an important source of domestic food and nutrition security while providing income for nearly 80% of Ethiopians. However, several infectious and parasitic diseases hamper poultry production. To date, evidence on the nationwide burden of specific diseases has not been collated to inform targeting of poultry health interventions. The objective of this systematic review is to summarize and analyze the literature on poultry diseases since 2000. A detailed systematic review protocol was designed according to Cochrane collaboration, Strengthening the Reporting of Observational Studies in Epidemiology (STROBE), and the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) statements. The review revealed that 14 infectious and parasitic diseases of poultry were reported in 110 published studies from 2000 to 2017, and 81.82% (90/110) of the studies covered 6 diseases: Newcastle disease (ND), infectious bursal disease (IBD), avian coccidiosis, helminth infestation, ecto-parasite infestation, and Salmonella infection. The pooled prevalence estimates of ND and IBD were 44% (95% confidence interval [CI]: 27 to 63) and 41% (95% CI: 23 to 60), respectively. Among the parasitic diseases, avian coccidiosis, helminth infestation, and ecto-parasite infestation had estimated pooled prevalences of 37% (95% CI: 30 to 44), 62% (95% CI: 45 to 78), and 50% (95% CI: 33 to 68), respectively. The pooled prevalence estimate of Salmonella infection was found to be 51% (95% CI: 32 to 70). Most of the studies were conducted in central Ethiopia, in the State of Oromia, and focused on extensive farming systems. While the number of studies was low, the overall trend of disease reporting in the literature is increasing (Y = 0.99X-3.34). In conclusion, the high-pooled prevalence estimates of diseases and the scarcity of reported data for all of Ethiopia indicate an important data gap on infectious-disease distribution in the country. While the high-pooled prevalence points towards the need for intervention to control poultry diseases, there is also a need to ensure all diseases that result in production losses and public health risks are studied appropriately in all Ethiopian production systems.